A rare co-existence of helicobacter pylori, candida albicans and candida keyfr in a giant gastric ulcer - Ali Tüzün İnce and Orhan Kocaman and Medina İsmailova and Mukaddes Tozlu and Zühal Gücin and Meryem İraz (Turkish Journal of Gastroenterology, 2019)
-